MOORING SYSTEM DESIGN AND MOTION ANALYSIS OF KAMPUNG LAUT CILACAP FLOATING BRIDGE - Reza Subagja - NIM 15513046 , Mochamad
The mooring system is a system for maintaining the stability of a floating structure from the influence of the environmental forces acting on the structure. A mooring system has design criteria that must be fulfilled by the mooring line. In addition, the floating structure that becomes the object of this research is the floating bridge, so it needs additional design criteria that the user comfort of the bridge seen from the translational acceleration of floating bridge structure. Therefore, in this study will be discussed about the mooring system and motion response analysis that occurs on a floating bridge. The tidal conditions of the waters and the full-empty load on the structure become the condition being examined. In addition, the mooring system is checked during intact and damaged conditions. In this research, floating structure modeling and mooring system is done using HydroStar and Ariane7 software. The environmental force applied in this study is the wave force due to the movement of the ship combined with the current force and the wind force. The analysis was carried out according to the standards in the API RP 2SK regarding design criteria for maximum tension of mooring line and DRDC Toronto TR 2006-229 as design criteria for maximum translational acceleration. The results of this study indicate that the tension of mooring line and acceleration of structures that occur in the mooring system fulfilled the design criteria, both in intact and damaged conditions.